Posttraumatic Growth pada Remaja Wanita yang Mengalami Kekerasan dalam Pacaran Ditinjau dari Perceived Social Support dan Variabel Demografi - Humaira Syahnya Almas; Chandradewi Kusristanti (Journal An-Nafs: Kajian Penelitian Psikologi, 2021)
Dating violence cases are increasing every year in Indonesia. Despite violence being one of the traumatic events, it does not rule out the possibility that the survivors experienced growth after trauma called posttraumatic growth (PTG). This study aims to determine the contribution of perceived social support (PSS) towards posttraumatic growth (PTG) among adolescent women who experienced dating violence (n = 308). This research is a quantitative study, with an F-Soz U K-14 questionnaire (Î± = 0.817) to measure PSS and PTGI-SF scale (Î± = 0.89) to measure PTG. Using statistical regression was found that PSS had a significant role towards PTG (R2 = .186, p = .000). The result of this study can be useful as a basis in educating the importance of support given by significant others for adolescent women exposed to violence during or after the violence happened.